Effect of a carotenoid-producing Bacillus strain on intestinal barrier integrity and systemic delivery of carotenoids: A randomised trial in animals and humans. (May 2021) - Stevens, Yala; Pinheiro, Iris; Salden, Bouke; Duysburgh, Cindy; Bolca, Selin; Degroote, Jeroen; Majdeddin, Maryam; Van Noten, Noémie; Gleize, Béatrice; Caris-Veyrat, Catherine; Michiels, Joris; Jonkers, Daisy; et al.
Graphical abstract: Highlights: PD01 survived passage through the GI tract in piglets and in human subjects. PD01 supplementation resulted in accumulation of PD01 carotenoids in human plasma. PD01 intake resulted in improved barrier function outcomes in early weaned piglets. PD01 did not significantly affect GI permeability in overweight/obese subjects. Abstract: The aim of the present study was to investigate effects of the carotenoid-producing Bacillus indicus strain PD01 on intestinal barrier function and its ability to survive passage through the gastrointestinal tract and to assess systemic bioavailability of these carotenoids in vivo . As model for impaired barrier function, 16 early weaned piglets were randomly assigned to a control diet or control diet with PD01 for 23 days. In addition, 67 overweight/obese, otherwise healthy individuals were randomly assigned to groups receiving PD01 or placebo for 6 weeks. PD01 survived passage through the gastrointestinal tract in piglets and human subjects and resulted in significant accumulation of PD01 derived carotenoids (methyl-glycosyl-apo-8′-lycopenoate and glycosyl-apo-8′-lycopene) in human plasma after 3- and 6-weeks supplementation versus baseline (0.044 and 0.076 vs 0 µM, respectively; p < 0.001). PD01 supplementation resulted in higher expression levels of occludin in the distal small intestine (1.38 ± 0.31 vs 0.59 ± 0.14; p = 0.044) and transepithelial electrical resistance in the mid colon (34.1 ± 3.01 vs 24.3 ± 1.13 Ω.cm 2 ; p = 0.019) of early weaned piglets compared to control. In overweight/obese individuals with preserved barrier integrity, PD01 did not affect sugar excretion (p ≥ 0.104). In summary, PD01 survived transit through the gastrointestinal tract, resulted in systemic carotenoid accumulation and improved compromised barrier function outcomes.